2023
DOI: 10.1002/adhm.202201555
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid‐on‐a‐Chip: An Organoid Platform for In Vitro Assessment of Endocrine Disruption

Abstract: Thyroid is a glandular tissue in the human body in which the function can be severely affected by endocrine disrupting chemicals (EDCs). Current in vitro assays to test endocrine disruption by chemical compounds are largely based on 2D thyroid cell cultures, which often fail to precisely evaluate the safety of these compounds. New and more advanced 3D cell culture systems are urgently needed to better recapitulate the thyroid follicular architecture and functions and help to improve the predictive power of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…In a previous work, we have demonstrated that perfusion promotes the functionality of mESC‐derived thyroid organoids. [ 30 ] However, on‐chip culture of organoids was difficult to execute, in part due to the high complexity of the microfluidic apparatus and time‐consuming cell culture protocols. In the present work, Matrigel‐embedded thyroid organoids (30–100 µm), were pre‐formed and cultured in microthermoformed carriers for three days under static conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous work, we have demonstrated that perfusion promotes the functionality of mESC‐derived thyroid organoids. [ 30 ] However, on‐chip culture of organoids was difficult to execute, in part due to the high complexity of the microfluidic apparatus and time‐consuming cell culture protocols. In the present work, Matrigel‐embedded thyroid organoids (30–100 µm), were pre‐formed and cultured in microthermoformed carriers for three days under static conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The FCBs occupied a total volume of 1.3 L (excluding pump) and allowed a minimal used tubing length of 34 cm per FCB, which corresponded to a 64% drop as compared to our previously used OoC platform. [ 30 ] This decrease in tubing and connectors yielded 15× shorter assembly times of microfluidic peripherals (Figure S8, Supporting Information), facilitating the assembly of the total fluidic system by two operators within 2 h.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] Organoid models have gradually matured and become prominent in recent years. [6][7][8][9] Compared with traditional monolayer culture and animal models, organoids are able to partially reproduce key physiological features of the native human organs, including cell heterogeneity, spatial structure and microenvironment, and provide important cell-cell and extracellular matrix (ECM) interactions. 10,11 These can promote hepatocyte proliferation, differentiation, expression of specific genes and proteins, and response to exogenous stimuli.…”
Section: Introductionmentioning
confidence: 99%